Myeloablative autologous haematopoietic stem cell transplantation resets the B cell repertoire to a more naïve state in patients with systemic sclerosis. Issue 3 (14th October 2022) - Adamska, Julia Z; Zia, Amin; Bloom, Michelle S; Crofford, Leslie J; Furst, Daniel E; Goldmuntz, Ellen; Keyes-Elstein, Lynette; Mayes, Maureen D; McSweeney, Peter; Nash, Richard A; Pinckney, Ashley; Welch, Beverly; et al.
Abstract : Objectives: Myeloablative autologous haematopoietic stem cell transplant (HSCT) was recently demonstrated to provide significant benefit over cyclophosphamide (CYC) in the treatment of diffuse cutaneous systemic sclerosis (dcSSc) in the Scleroderma: Cyclophosphamide or Transplantation (SCOT) trial. As dysregulation of the B cell compartment has previously been described in dcSSc, we sought to gain insight into the effects of myeloablative autologous HSCT as compared with CYC. Methods: We sequenced the peripheral blood immunoglobulin heavy chain (IGH) repertoires in patients with dcSSc enrolled in the SCOT trial. Results: Myeloablative autologous HSCT was associated with a sustained increase in IgM isotype antibodies bearing a low mutation rate. Clonal expression was reduced in IGH repertoires following myeloablative autologous HSCT. Additionally, we identified a underusage of immunoglobulin heavy chain V gene 5–51 in patients with dcSSc, and usage normalised following myeloablative autologous HSCT but not CYC treatment. Conclusions: Together, these findings suggest that myeloablative autologous HSCT resets the IGH repertoire to a more naïve state characterised by IgM-expressing B cells, providing a possible mechanism for the elimination of pathogenic B cells that may contribute to the benefit of HSCT over CYC in the treatment of dcSSc.